Kenya - Karwe Village - Makengi - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
Anastacia Muthoni tells the crew of the videoseries 'Farmer Testimonials' how the climate has changed in Kenya and how she is now struggling to find and get sufficient water to harvest enough for her family. The weather has really changed in Kenya the last few years, she says.